Análise das relações filogenéticas entre as espécies de Euglossa Latreille, 1802 ( Hymenoptera: Apidae: Euglossina), com ênfase nos subgêneros Glossura Cockerell, 1917 e Glossuropoda Moure, 1989 - Rafael Rodrigues Ferrari (2017)
The bee genus Euglossa Latreille, 1812 (Hymenoptera: Apidae: Apini) is the most diversified in the subtribe Euglossina, comprising 140 valid species included in seven recognized subgenera: Alloglossura Hinojosa-Díaz & Engel, 2012, Dasystilbe Dressler, 1978b, Euglossa s.str., Euglossella Moure, 1967, Glossura Cockerell, 1917, Glossurella Dresller, 1982b and Glossuropoda Moure, 1989. Some recent phylogenetic studies have suggested that the infrageneric classification of Euglossa comprises, at least partly, artificial groups that would need to be phylogenetically redefined. Based on this panorama, this dissertation investigated the phylogenetic relationships of the Euglossa species, with emphasis on those belonging to subgenera Glossura and Glossuropoda. Fifty-five species were included, 47 of them representing the main lineages of Euglossa and eight representing outgroups. Morphological characters were surveyed under stereoscopic microscope, and DNA sequences of four genes, three nuclear and one mitochondrial, were obtained from the NCBI GeneBank. Phylogenetic analyses were carried out using parsimony and Bayesian inference with 3448 characters (126 morphological and 3322 molecular). The subgenera Euglossa s.str., Euglossela and Glossuropoda were retrieved as monophyletic. Euglossella was recovered as the sistergroup of the remaining Euglossa. Glossuropoda comprises six species in three groups: intersecta (Eg. intersecta and Eg. cyanochlora), rugilabris (Eg. inflata, Eg. juremae and Eg. rugilabris) and nigrosignata (Eg. nigrosignata [reincluded in Glossuropoda]). The subgenera Alloglossura and Glossurella are artificial groups, so they need to be redefined. Euglossa (Glossura) stellfeldi was considered incertae sedis allowing Glossura to be monophyletic. Glossura comprises 17 species distributed in four groups: allosticta (Eg. allosticta Moure, 1969 and Eg. viridifrons Dressler, 1982b), asarophora (Eg. asarophora Moure & Sakagami in Moure, 1969, Eg. natesi Parra-H, Ospina-Torres & Ramírez, 2005 and Eg. rufipes Rasmussen & Skov, 2006), piliventris (Eg. lugubris Roubik, 2004, Eg. piliventris Guérin-Méneville, 1844 and Eg. tiputini Roubik, 2004) and orellana (Eg. bazinga Nemésio & Ferrari, 2012, Eg. chalybeata Friese, 1925, Eg. flammea Moure, 1969, Eg. ignita Smith, 1874, Eg. imperialis Cockerell, 1922, Eg. iopoecila Dressler, 1982a, Eg. occidentalis Roubik, 2004, Eg. orellana Roubik, 2004 and Eg. roubiki Nemésio, 2009a).